2019
DOI: 10.1177/0733464819842500
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Reliant Umbrella: Defining Successful Aging Among the Old-Old (80+) in Shanghai

Abstract: The Chinese old-old (80+) population has steadily increased in recent years; however, limited studies have examined how this group ages. The purpose of this study is to explore how the old-old in urban China define successful aging. Guided by grounded theory, we conducted semi-structured, in-depth interviews with community-dwelling old-old participants (N = 97). Participants identified self-reliance as the goal of successful aging, which was supported by four proactive behaviors: physical activity, financial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 47 publications
0
43
0
1
Order By: Relevance
“…Nine studies that reported frameworks of healthy ageing were included in the review (Fig. 1) [13][14][15][16][17][18][19][20][21].…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies that reported frameworks of healthy ageing were included in the review (Fig. 1) [13][14][15][16][17][18][19][20][21].…”
Section: Study Selectionmentioning
confidence: 99%
“…All studies were found to be of high quality according to the CASP Checklist for qualitative studies and the NOS for cross-sectional studies (Supplementary Table 2, Supplementary Table 3). Five qualitative studies did not adequately report the relationship between the researcher and the participants [14][15][16][17][18][19][20][21]. Two cross-sectional studies did not report the comparability between respondents and non-respondents [13,18].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations